Analisis Bibliometrik Terhadap Impulse Buying - Utama, Ari Kusuma Budi (STIE PENA, 2023)
Impulse buying is a buying process made by consumers without thinking about the need for a product and not going through the search stage information about a product and very strong emotional factor. Impulse buying by consumers has received considerable attention in consumer research. The phenomenon is interesting because it is not only prompted by a variety of internal psychological factors but also influenced by external, market-related stimuli. This study attempts to analyze online marketing from 2018 to 2022 through a bibliometric analysis procedure. A total of 200 articles were published retrieved from the Google Scholar database for analysis. This study uses a quantitative method take advantage of Publish or Perish software, Google Scholar, VOSViewer and Mendeley. Impulse buying behavior occurs because of stimulation from stores or retailers that offer attractive goods, resulting in an urge to buy more.Keywords : Bibliometric; Impulse Buying; Impulse Buying Behavior